Uncover Communication Strategy in Islamic Center Islamic Boarding School Bin Baz Yogyakarta in Indonesia - Robbaniyah, Qiyadah; Lina, Roidah; Anam, Syaiful (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
Communication plays an important role in the organization of Islamic boarding schools. The purpose of this research is to find out the communication strategy at the Islamic Center Bin Baz Islamic Boarding School. The research method uses qualitative research, this type of field research, interview data collection, documentation and observation. Data analysis by presenting the data obtained, classifying the data and entering the data into sub-sections, analyzing the data obtained. The results of the study at the Bin Baz Islamic Center Islamic Boarding School used a communication strategy to students more by using direct communication (face to face), and to the guardians of students by using individual communication via cell phone/online or in general by using zoom media/group wa/fb. Implementation of bonding activities by assisting students with small groups, the task of the homeroom teacher is also the guardian of the dormitory, and strengthening activities between ustadzah and students. The positive effect of bonding between ustdzah and santri is that the ustadzah recognizes female students from their backgrounds, etc. student violations decreased. The culture that is built in communication at Islamic boarding schools is a way of communicating between ustdzah and female students with good and positive speech and language.